Effects of student collaboration on ESL learners' vocabulary development / Adlina Ariffin - Ariffin, Adlina (2021)
This paper describes the effectiveness of student collaboration as a technique in improving vocabulary development among a group of ESL learners. The main motivation behind this study was the concern that vocabulary has become a neglected area in the teaching of English language. The main aims of the study were to evaluate whether student collaboration helped to improve students' vocabulary and the extent of the improvement. Two types of data were collected during the research - qualitative and quantitative. The qualitative data were collected from the teacher's observation, students' journals and interview; while, the quantitative data were collected from the pre-test and post-test. The results from the t-test indicated that students did make an improvement in their vocabulary knowledge after they had studied together collaboratively. Besides that, student collaboration was found to be an effective technique in teaching vocabulary because the interaction that students made during their discussion helped them to improve other language skills such as reading, listening and speaking, gave them opportunities to participate in their own learning, built their self-confidence in interacting with the group members and cultivated a sharing attitude among them.